2002
DOI: 10.4489/myco.2002.30.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Biologically Active Compounds for Control of Wheat Root Rot and its Causal Pathogens

Abstract: The main aim of this study is to evaluate the efficiency of two biologically active compounds (Strom and F-760) in control of wheat root rot disease and its causal organisms. Fusarium graminearum, F. oxysporum, F. solani and Bipolaris sorokiniana were used as target organisms. In vitro, the two compounds showed fungicidal effect on all investigated pathogens resulted in suppression of radial growth and mycelial dry weight of them. Under greenhouse conditions, treatment of wheat grains with either Strom or F-76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…It was also observed that the percentages of damping-off in all tested fungi were higher than those of root rot. These results are in harmony with those reported by Asran andEraky (2011), Atef (2008) and Hashem and Hamada (2002 Hashem and Hamada, 2002;Nourozian et al, 2006;Soleimani et al, 2005). According to Harman (2001) natural factors limiting the number of soil borne pathogens occur through a combination of antagonism by other soil fungi and bacteria, natural release of antibiotics from other bacteria and fungi, and by competitive exclusion of habitat in the root zone or rhizosphere.…”
Section: Pathogenicity Testssupporting
confidence: 91%
See 2 more Smart Citations
“…It was also observed that the percentages of damping-off in all tested fungi were higher than those of root rot. These results are in harmony with those reported by Asran andEraky (2011), Atef (2008) and Hashem and Hamada (2002 Hashem and Hamada, 2002;Nourozian et al, 2006;Soleimani et al, 2005). According to Harman (2001) natural factors limiting the number of soil borne pathogens occur through a combination of antagonism by other soil fungi and bacteria, natural release of antibiotics from other bacteria and fungi, and by competitive exclusion of habitat in the root zone or rhizosphere.…”
Section: Pathogenicity Testssupporting
confidence: 91%
“…could be effectively used in suppressing diseases caused by Fusarium spp. Drechslera halodes and Rhizoctonia solani as reported by many workers (Abdel-Monaim, 2010;Hashem and Hamada, 2002;Nourozian et al, 2006;Soleimani et al, 2005). Modes of action for beneficial micro-organisms include direct parasitism removed from the soil, washed thoroughly to remove soil debris, root-rot were recorded as follows: 0 = roots without discoloration (no infection); 1= 1-20%; 2= 21-40%; 3= 41-75%; 4= 75-100% discoloration root mass and 5= completely dead plants include pre-or post emergence damping-off or old plants for each replicate.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several fungi were recorded as pathogens of seed and root-rot diseases on wheat such as Alternaria alternata, Fusarium spp. (F. culmorum F. graminearum, F. equiseti and F. solani) Pyrenophora tritici-repentis and Rhizoctonia solani (El-Kholy, 1999, Hashem andHamada-Afaf, 2002;Atef-Nagwa, 2008;Asran and El-Eraky-Amal, 2011;Harvey et al, 2015 andEl-Ballat, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among seedling diseases of wheat, damping-off and/or root rot caused by several soil-borne fungi F. solani, F.oxysporium, F. graminearum, Pythiumsp. and R. solani that attack at seedling stages of crop and directly reduce plant population as well as yield of wheat (Hashem and Hamada, 2002;Abdelzaher, 2004;Atef, 2008;Ahmed et al, 2009;Asran andEraky, 2011 andMoubarak andAbdel-Monaim 2011). Control of damping-off mainly depends on fungicide treatment.…”
Section: Introductionmentioning
confidence: 99%